1993
DOI: 10.1111/j.1365-2044.1993.tb07481.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bicore pulmonary monitor

Abstract: SummaryThe Bicore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Patient and ventilator variables were measured with a pulmonary mechanics monitor incorporating Campbell diagram software (Bicore CP-100, Viasys Healthcare, Palm Springs, CA). The precision and accuracy of this monitor have been previously validated (14,15). The monitor and transducers were calibrated before each study.…”
Section: Methodsmentioning
confidence: 99%
“…Patient and ventilator variables were measured with a pulmonary mechanics monitor incorporating Campbell diagram software (Bicore CP-100, Viasys Healthcare, Palm Springs, CA). The precision and accuracy of this monitor have been previously validated (14,15). The monitor and transducers were calibrated before each study.…”
Section: Methodsmentioning
confidence: 99%
“…Online supplemental table S1 which summarises the main characteristics of 17 physiological studies evaluating different SBTs, suggests that mechanical ventilation allows to unload the respiratory muscles 3 8–14 17 19 21. As the amount of support provided by the given SBTs’ modality increases (assisted trials), the workload of patient’s respiratory muscles decreases.…”
Section: Discussionmentioning
confidence: 99%
“…A physiological meta-analysis from Sklar et al published in 2017,3 including 16 studies and 239 patients, reported that PSV reduces respiratory effort compared with T-piece trial which reflected physiological conditions after extubation more accurately. However, the authors conclude that these results are tempered by the limited number of studies, the small number of patients included in each and by methodological heterogeneity 8–23. The authors of this meta-analysis3 stated that further investigations are therefore necessary.…”
Section: Introductionmentioning
confidence: 97%